Социальная и политическая сатира в романе В. Аксенова „Остров Крым” - Murawski, Antoni (Studia Rossica Posnaniensia, 2014)
This article is devoted to analyzing the use of satire and parody in Vasily Aksyonov’s novel The Island of Crimea (1979). The author of this article presents a variety of aspects concerning the meaning of comic elements that were used by the writer to show the dissonance between reality and the idealistic as well as subjective perception of a difficult political and social environment.